Mother and Family’s View on Exclusive Breastfeeding in Developing Country - Iqbal Pramukti; Michael Hill; Norehan Binti Mohammad Isa (Jurnal Keperawatan Padjadjaran, 2014)
Exclusive breastfeeding is something which has a lot of benefit both for mother and baby. It is recommended by WHO at let for the first six months. Then it also recommended until two years and beyond. In fact, mostly mother only gave their breastmilk to their babies until two months. The method of this study using systematic review-metasynthesize which an extensive of the literature was undertaken. Database searched were: MEDLINE, CINAHL, BioMed Central, Wiley, and EMBASE. Result shown that mother’s view on exclusive breast is an important part in an attempt to promote breastfeeding desire. Even though their view is influenced by her family and surroundings, but finally the decision is on her. This concurs with finding of some researcher who found women who have the experience of breastfeeding, especially within the family, are more likely to choose to breastfeed heir child.Key words:Exclusive breastfeeding, family, mother AbstrakPemberian ASI eksklusif adalah sesuatu yang memiliki manfaat sangat besar baik bagi ihu maupun bayi. Hal ini sangat direkomendasikan oleh WHO minimal sampai enam bulan pertama kelahiran bayi. Kemudian dapat dilanjutkan sampai usia dua tahun. Pada kenyataannya, kebanyakan ibu memberikan ASI mereka kepada bayinya hanya sampai usia bayi dua bulan. Metode yang digunakan adalah systematic review- metasintesisyang mana menggunakan pencarian literatur secara luas. Database yang dipilih adalah: MEDLINE, CINAHL, BioMed Central, Wiley, dan EMBASE. Hasil penelitian menunjukkan bahwa pandangan ibu mengenai pemberian ASI eksklusif memiliki peranan yang penting dalam usaha meningkatkan keinginan untuk menyusui. Walaupun pandangan mereka dipengaruhi oleh keluarga dan sekitarnya, namun keputusan akhir tetap berada di tangan mereka. Hal ini sejalan dengan beberapa penelitian yang sudah dilakukan oleh beberapa peneliti sebelumnya yang menyebutkan bahwa wanita yang memiliki pengalaman dalam menyusui, khususnya di dalam keluarga akan cenderung memutuskan untuk menyusui bayinya.Kata kunci:ASI eksklusif, keluarga, ibu